Anesthesiology : a Comprehensive Review for the Written Boards and Recertification. - Matthes, Kai (Oxford University Press, 2013)
Anesthesiology: A Comprehensive Review for the Written Boards and Recertification is a high-yield, streamlined study aid. It contains more than 1000 updated, realistic multiple-choice questions tailored to the question content of recent American Board of Anesthesiology (ABA) exams. To maximize reading efficiency, key messages are repeated and highlighted in the bullets. While focusing on most-frequently tested keywords by the ABA, this book also covers new ""emerging"" topics such as patient safety, statistics, and ethics. Well-chosen illustrations and graphs are used to enhance the learning e.